Strategies for improving production performance of probiotic Pediococcus acidilactici viable cell by overcoming lactic acid inhibition - Othman, Majdiah; Ariff, Arbakariya; Wasoh, Helmi; Kapri, Mohd Rizal; Halim, Murni (Springer Open, 2017)
Lactic acid bacteria are industrially important microorganisms recognized for fermentative ability mostly in their probiotic benefits as well as lactic acid production for various applications. Fermentation conditions such as concentration of initial glucose in the culture, concentration of lactic acid accumulated in the culture, types of pH control strategy, types of aeration mode and different agitation speed had influenced the cultivation performance of batch fermentation of Pediococcus acidilactici. The maximum viable cell concentration obtained in constant fed-batch fermentation at a feeding rate of 0.015 L/h was 6.1 times higher with 1.6 times reduction in lactic acid accumulation compared to batch fermentation. Anion exchange resin, IRA 67 was found to have the highest selectivity towards lactic acid compared to other components studied. Fed-batch fermentation of P. acidilactici coupled with lactic acid removal system using IRA 67 resin showed 55.5 and 9.1 times of improvement in maximum viable cell concentration compared to fermentation without resin for batch and fed-batch mode respectively. The improvement of the P. acidilactici growth in the constant fed-batch fermentation indicated the use of minimal and simple process control equipment is an effective approach for reducing by-product inhibition. Further improvement in the cultivation performance of P. acidilactici in fed-bath fermentation with in situ addition of anion-exchange resin significantly helped to enhance the growth of P. acidilactici by reducing the inhibitory effect of lactic acid and thus increasing probiotic production.